Planning and designing effective web sites - Conger, Sue A.; Mason, Richard O. (Cambridge, MA : Course Technology, 1998)
This book is divided into four parts: Behind the WEB; Preparation; Design Methods; and Ongoing Support for Planning and Designing Effective WEB Sites.
Keywords: Computer; Design; Web sites; Web sites -- Design